A cost-effective solution to security constrained dispatch problem of Islanded microgrid using chaotic spotted Hyena optimization. Issue 1 (2nd January 2023) - Mishra, Tanuj; Singh, Amit Kumar; Kamboj, Vikram Kumar
ABSTRACT: Power system network is growing day by day as per the increased demand due to technological development around the globe. The increased power demand needs optimized planning for all the sections of power system. Economic dispatch is one of the important areas in which new optimization techniques can add to the overall improvement in the power system planning. Recent technological improvement in microgrids results in economic and efficient operation considering both conventional and non-conventional methods of generation. This paper highlights the optimal scheduling requirement in the advanced power system control by introducing a new proposed metaheuristic hybrid approach, i.e., Chaotic Spotted Hyena Optimization (CSHO). The proposed approach improves and intensifies the conventional approach and the results obtained are compared with some well-known published approaches using standard data. The CSHO is implemented on an islanded microgrid having five distributed generators out of which three are conventional generators and two are renewable sources. Three objectives are tested on the microgrid-(1) Economic scheduling, (2) Environmental emission and (3) CEED for Microgrid and the results of proposed approach are tested in four scenarios and compared with the PSO, DE, SOS, GWO and WOA approaches. The result achieved from the proposed approach is remarkable over previous approaches and showing enhanced economic operation, which are verified and presented in different sections of paper.